Proceedings of the Twenty-Ninth International Joint Conference on Artificial Intelligence 2020
DOI: 10.24963/ijcai.2020/600
|View full text |Cite
|
Sign up to set email alerts
|

An Exact Single-Agent Task Selection Algorithm for the Crowdsourced Logistics

Abstract: The trend of moving online in the retail industry has created great pressure for the logistics industry to catch up both in terms of volume and response time. On one hand, volume is fluctuating at greater magnitude, making peaks higher; on the other hand, customers are also expecting shorter response time. As a result, logistics service providers are pressured to expand and keep up with the demands. Expanding fleet capacity, however, is not sustainable as capacity built for the peak seasons would be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In evaluating future purchase intention, Garbarino and Johnson (1999) concluded that for different types of consumers, three aspects of relationship quality can be separately defined and treated independently that is, overall consumer satisfaction, trust and commitment, In particular, they proposed that overall consumer satisfaction could affect trust and, in effect, trust could affect commitment. A customer's perceived trust in a site can affect his/her willingness to take the risk of buying something that he/she cannot physically inspect (Han & Cheng, 2020). Marriott, Williams, and Services (2018) have shown that trust in online merchants can increase consumers' willingness to shop online.…”
Section: • (H4-3): Website Quality Will Have a Positive Effect On Satisfaction The Relationship Between Relationship Quality And Repurchamentioning
confidence: 99%
“…In evaluating future purchase intention, Garbarino and Johnson (1999) concluded that for different types of consumers, three aspects of relationship quality can be separately defined and treated independently that is, overall consumer satisfaction, trust and commitment, In particular, they proposed that overall consumer satisfaction could affect trust and, in effect, trust could affect commitment. A customer's perceived trust in a site can affect his/her willingness to take the risk of buying something that he/she cannot physically inspect (Han & Cheng, 2020). Marriott, Williams, and Services (2018) have shown that trust in online merchants can increase consumers' willingness to shop online.…”
Section: • (H4-3): Website Quality Will Have a Positive Effect On Satisfaction The Relationship Between Relationship Quality And Repurchamentioning
confidence: 99%